Rechargeable anticandidal denture material with sustained release in saliva. (10th March 2016) - Malakhov, A; Wen, J; Zhang, B‐X; Wang, H; Geng, H; Chen, X‐D; Sun, Y; Yeh, C‐K
Abstract : Objective: Candida ‐induced denture stomatitis is a common debilitating problem among denture wearers. Previously, we described the fabrication of a new denture material that released antifungal drugs when immersed in phosphate buffered saline. Here, we use more clinically relevant immersion conditions (human saliva; 37°C) and measure miconazole release and bioactivity. Materials and Methods: Disks were prepared by grafting PNVP [poly(N‐vinyl‐2‐pyrrolidinone)] onto PMMA [poly(methylmethacrylate)] using plasma initiation (PMMA‐g‐PNVP) and then loaded with miconazole. Drug‐loaded disks were immersed in 10–100% human saliva (1–30 days). Miconazole release was measured and then tested for bioactivity vs miconazole‐sensitive and miconazole‐resistant Candida isolates. Results: HPLC was used to quantify miconazole levels in saliva. Miconazole‐loaded disks released antifungal drug for up to 30 days. Higher drug release was found with higher concentrations of saliva, and, interestingly, miconazole solubility was increased with higher saliva concentrations. The released miconazole retained its anticandidal activity. After immersion, the residual miconazole could be quenched and the disks recharged. Freshly recharged disks displayed the same release kinetics and bioactivity as the original disks. Quenched disks could also be charged with chlorhexidine that displayed anticandidal activity. Conclusions: These results suggest that PMMA‐g‐PNVP is a promising new denture material for long‐term management of denture stomatitis.